THE CORRELATION BEETWEN PERCEPTION TO ORGANIZATION WITH INTEREST BECOME LEADER IN STUDENT OF DIPONEGORO UNIVERSITY - Aziz Nugroho; Jati Ariati (Jurnal EMPATI, 2014)
The study aims to find the correlation between perception to organization with interest become leader in student of Diponegoro University (Undip). The Subjek were member of the Unit Kegiatan Mahasiswa (UKM) at Undip. The sample consisted of 135 student was spread over in 9 UKM, with sampling technique used cluster random sampling. Retrieval of data used  interest become leader scale ( 27 aitem with α = 0,869) and perception to organization scale ( 31 aitem with α = 0,876) which previously have been  tested on 200 student in 11 organizations.The items were analyzed by simple regression analysis and showed correlation coefficient value at 0,632 with p=0,00 ( p<0,05). These result indicate there is significant correlation between perception to organization with interest become leader in student of  Diponegoro University. Perception to organization effective contribution 39,9% to interest become leader.